(untitled) (Central Medical College Journal, 2026)
Background: Piriformis syndrome (PS) is an entrapment neuropathy due to irritation or compression of the sciatic nerve by the piriformis muscle. Its presentation frequently mimics Prolapsed Lumbar Intervertebral Disc (PLID) and may coexist with it, complicating diagnosis. Case: We report a 30-year-old male with buttock-predominant sciatica persisting after PLID directed Epidural injection. Clinical examination (positive Freiberg, FAIR) and imaging supported Piriformis Syndrome. Ultrasound-guided piriformis injection using 2 mL of 1% lidocaine plus a structured rehabilitation protocol produced rapid and sustained pain reduction (VAS 8→2 at 3 months). Conclusion: In patients with ongoing sciatica despite appropriate PLID management, targeted evaluation for PS is warranted. Ultrasound-guided injection combined with rehabilitation is effective for both diagnosis and treatment. Central Medical College Journal Vol 9 No 2 July 2025 Page: 125-127